Plant extracts in the control of plant pathogens seeds and fusariosis in okra - Mônica Shirley Brasil dos Santos e Silva; Antônia Alice Costa Rodrigues; Anna Christina Sanazário de Oliveira; Erlen Keila Cândido e Silva; Larisse Raquel Carvalho Dias; Natalia de Jesus Ferreira Costa; Mônica Shirley Brasil dos Santos e Silva; Antônia Alice Costa Rodrigues; Anna Christina Sanazário de Oliveira; Erlen Keila Cândido e Silva; Larisse Raquel Carvalho Dias; Natalia de Jesus Ferreira Costa (Revista Ceres, 2023)
ABSTRACT The objective of this study was to assess seed health and the effect of plant extracts on Fusarium oxysporum f. sp. vasinfectum mycelial growth and sporulation, plant pathogen reduction in seeds and fusariosis control in okra seedlings. Health was assessed by the Blotter Test, after immersing the seeds in natural extracts and plating. To verify the mycelial growth of the plant pathogen, the extracts were incorporated in PDA culture medium and the pathogen was added and assessed, including the spore count. In the greenhouse, the seeds were immersed in the extracts, sown and at 15 days they were sprayed with extracts, at 21 days inoculated with the pathogen and disease severity on the seedlings was assessed 7 days later. There were higher incidences of Fusarium sp. and Rhizopus stolonifer in the seeds of the cultivars Valença and Santa Cruz 47. The extracts that resulted in lower pathogen incidence was basil, in cv. Valença and cinnamon and neem, in cv. Santa Cruz 47. The neem treatment presented the best inhibition percentage and the lowest sporulation mean in mycelial growth of the pathogen. Neem presented higher disease incidence control in the seedlings of cv. Valença and basil on the seedlings of cv. Santa Cruz 47.